1993
DOI: 10.1254/jjp.63.65
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Calcium Ion on Testis Carbonyl Reductase in Rats

Abstract: ABSTRACT-To examine the role of carbonyl reductase (CR) in the development and function of testis, age-related changes in CR and the effect of exogenous calcium on CR in rat testis were studied. Testicular CR activity was the highest at 3 weeks of age when the enzyme activity was measured at 2, 3, 4, 8 and 20 weeks of age. The intensity of positive protein bands in testicular cytosol was similar among these age groups in Western blot analysis with anti-rat ovarian CR antibody. In 3-week-old rats, intravenous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…To our knowledge, there are no reports concerning age-related changes of  hepatic CBR1 and AKR1C activities and/or expressions. Only Inazu and Fujii [43] reported that activity of rat testicular carbonyl reductase reached a peak value at 3 weeks, then it steeply declined at 4 weeks, and did not further change between 4 and 20 weeks of age. …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no reports concerning age-related changes of  hepatic CBR1 and AKR1C activities and/or expressions. Only Inazu and Fujii [43] reported that activity of rat testicular carbonyl reductase reached a peak value at 3 weeks, then it steeply declined at 4 weeks, and did not further change between 4 and 20 weeks of age. …”
Section: Discussionmentioning
confidence: 99%
“…We have found that exogenous calcium has biphasic effects on testicular CR activity in 3-week-old rats but not in older animals (17). The results that Px offspring delays the aging process of hypothalamo-pituitaryovarian axis described by Fujii and Yamamoto (2) are of interest.…”
Section: Discussionmentioning
confidence: 73%
“…Enzyme expression in the ovary is modulated by estrogens and corticosteroids (Inazu et aI., 1990; and Ca 2 +ions and testosterone appear to influence the expression in the testes (Inazu and Fujii, 1993). These findings strongly suggested a role of the rat enzyme in steroid-modulated pathways or steroid metabolism itself.…”
Section: Introductionmentioning
confidence: 99%